Genetic variations in the retrograde endocannabinoid signaling pathway in Chinese patients with major depressive disorder - Xu, Huifang; Li, Tongtong; Gong, Qiyong; Xu, Haizhen; Hu, Yongbo; Lü, Wenqi; Yang, Xin; Li, Jin; Xu, Wenming; Kuang, Weihong (Frontiers in Neurology, 2023)
Background: The retrograde endocannabinoid (eCB) pathway is closely associated with the etiology of major depressive disorder (MDD) at both pathophysiological and genetic levels. This study aimed to investigate the potential role of genetic mutations in the eCB pathway and underlying mechanisms in Han Chinese patients with MDD. Methods: A total of 96 drug-naïve patients with first-episode MDD and 62 healthy controls (HCs) were recruited. Whole-exome sequencing was performed to identify the gene mutation profiles in patients with MDD. Results were filtered to focus on low-frequency variants and rare mutations (minor allele frequencies < 0.05) related to depressive phenotypes. Enrichment analyses were performed for 146 selected genes to examine the pathways in which the most significant enrichment occurred. A protein–protein interaction (PPI) network analysis was performed to explore the biological functions of the eCB pathway. Finally, based on current literature, a preliminary analysis was conducted to explore the effect of genetic mutations on the function of this pathway. Results: Our analysis identified 146 (15.02%) depression-related genetic mutations in patients with MDD when compared with HCs, and 37 of the mutations were enriched in the retrograde eCB signaling pathway. Seven hub genes in the eCB pathway were closely related to mitochondrial function, including Complex I genes (NDUFS4, NDUFV2, NDUFA2, NDUFA12, NDUFB11) and genes associated with protein (PARK7) and enzyme (DLD) function in the regulation of mitochondrial oxidative stress. Conclusion: These results indicate that genetic mutations in the retrograde eCB pathway represent potential etiological factors associated with the pathogenesis of MDD.